In her own time - Jung, Flora (Canadian Medical Education Journal, 2018)
As I look back on my first year as a medical student, I am dazed by the whirlwind of emotions and experiences I met within this short time. One recurring theme emerged from my first experiences in clinic. Younger and healthier patients are often asked to be our bedside teachers to facilitate our learning, but consequently, I found it uncannily natural to see myself in them. Each patient and their tale of tenacity, misery, sanguinity, and bravery would leave me lost in thought for days to follow. What if that were me?